2019
DOI: 10.1186/s43031-019-0006-9
|View full text |Cite
|
Sign up to set email alerts
|

Argumentation and interdisciplinarity: reflections from the Oxford Argumentation in Religion and Science Project

Abstract: Argumentation has emerged as a key area of research and development in science education in recent years. Simply defined, argumentation is about the justification of knowledge claims with evidence and reasons. Although there is now a vast amount of work in argumentation, much research remains to be pursued. Given the interdisciplinary nature of argumentation, the dialogue between science education and other relevant domains can potentially produce constructive research agendas that could profit argumentation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 58 publications
0
26
0
1
Order By: Relevance
“…Castéra and Clément 2014), research on argumentation in the context of the interphase of science education and RE is virtually inexistent (e.g. Erduran et al 2019). Furthermore, although there is research on science teachers' views about the science and religion comparison (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Castéra and Clément 2014), research on argumentation in the context of the interphase of science education and RE is virtually inexistent (e.g. Erduran et al 2019). Furthermore, although there is research on science teachers' views about the science and religion comparison (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Basel et al 2014) rather than pluralistic RE as in England. Furthermore, while argumentation in science education has been extensively researched (Lin et al 2018) and interest in interdisciplinarity is growing, much work remains to be done in terms of relating it to other traditionally disparate school subjects such as RE (Erduran et al 2019). Gaining a deeper understanding of the challenges and successes students experience when engaging in argumentation across these contexts is important because it allows us, in research and practice, to home in on the challenges and capitalise on the successes.…”
Section: Discussionmentioning
confidence: 99%
“…While the research literature on argumentation has been extensive in science education, interdisciplinary argumentation between science and other disciplines is less explored (Erduran et al 2019). Although there has been research on argumentation on science and religion debates (e.g.…”
Section: Interdisciplinary Argumentation and Transfermentioning
confidence: 99%
“…Besides, the use of argumentation activities in science classrooms (and in mathematics as well, Zhou, Liu, & Liu, 2021, but less frequently, Kartika, Budiarto & Fuad, 2021) can promote the spirit of inquiry, develop linguistic skills, foster students conceptual understanding and be helpful in performing interdisciplinary knowledge (Faize, Husain & Nisar, 2017;Lambert, & Bleicher, 2017;Erduran et al, 2019;Archila, Molina, & Truscott de Mejía, 2018) and different strategies has been described to reach this objective (Özdem et al, 2017, Erenler & Cetin, 2019. Based on the aforementioned reasons, the objective of this study is to analyze the consequences observed in students, when using entertaining science activities in the formal scientific subject contexts in secondary schools, following a based inquiry learning methodology and encourage their use in education work to improve students' interest and motivation for science.…”
Section: Theoretical Frameworkmentioning
confidence: 99%